Three prevention studies ongoing in Germany and Switzerland enrolling psychiatric patients at high risk for violence and compulsory hospitalization: Comparing aims, designs and methods. (May 2015) - Luckhaus, Christian; Lay, Barbara; Frommann, Nicole; Janssen, Birgit; Nitschke, Joachim
Abstract: Over the past decades, reductions of hospital beds and lengths of stay in general psychiatry are opposed to increases in detention cases and times in forensic psychiatric institutions. These developments raise the issue of trans-institutionalization of patient subgroups, whose particular needs of support are less accommodated by rationalized general psychiatry. While forensic psychiatric aftercare with a focus on risk assessment and assertive treatment has been largely established, preventive care of high-risk psychiatric patients to avert delinquency, compulsory hospitalization, or forensic courses has not yet been developed. Three outpatient studies addressing these issues have been conceptualized independently and were initiated in Germany and Switzerland. All three have similar study endpoints regarding incidence of violence, delinquency, compulsory hospitalization, and forensific sequelae. However, designs and methods differ with regard to inclusion criteria, assessment methods, foci of interventions, modes of delivering care, degrees of assertiveness, and times of follow-up. By the time of study completions, it can be expected that the joined information from all three studies will allow for a comprehensive appraisal of preventive treatment strategies and approaches in high-risk patients. In this paper, the study designs and methods of the three trials are outlined. Highlights: There is a paucity of prevention for psychiatric patients at high risk of violence. More knowledge is needed on specific treatment modules for preventing violence. Beyond treatment specification, efficacious delivery of treatment is relevant. Predictors need to be developed to identify relevant patient subgroups. Prospective intervention studies are needed to address the above issues empirically.